Interaction of therapeutic 12C ions with bone-like targets: physical characterization and dosimetric effect at material interfaces. (9th September 2021) - Colombi, S; Rovituso, M; Scifoni, E; Schuy, C; Eichhorn, A; Kraemer, M; Durante, M; La Tessa, C
Abstract: Carbon therapy is a promising treatment option for cancer. The physical and biological properties of carbon ions can theoretically allow for the delivery of curative doses to the tumor, while simultaneously limiting risks of toxicity to adjacent healthy structures. The treatment effectiveness can be further improved by decreasing the uncertainties stemming from several sources, including the modeling of tissue heterogeneity. Current treatment plans employ density-based conversion methods to translate patient-specific anatomy into a water system, where dose distribution is calculated. This approach neglects differences in nuclear interactions stemming from the elemental composition of each tissue. In this work, we investigated the interaction of therapeutic carbon ions with bone-like materials. The study concentrated on nuclear interactions and included attenuation curves of 200 and 400 AMeV beams in different types of bones, as well as kinetic energy spectra of all charged fragments produced up to 29 degrees from the beam direction. The comparison between measurements and calculations of the treatment planning system TRiP98 indicated that bone tissue causes less fragmentation of carbon ions than water. Overall, hydrogen and helium particles were found to be the most abundant species, while heavier fragments were mostly detected within 5 degrees from the beam direction. We also investigated how the presence of a soft tissue-bone interface could affect the depth-dose profile. The results revealed a dose spike in the transition region, that extended from the entry channel to the target volume. The findings of this work indicated that the tissue-to-water conversion method based only on density considerations can result in dose inaccuracies. Tissue heterogeneity regions containing bones can potentially produce dose spikes, whose magnitude will depend on the patient anatomy. Dose uncertainties can be decreased by modeling nuclear interactions directly in bones, without applying the tissue-to-water conversion.